364OClinical utility of ctDNA genomic alterations (GA) based on ESMO scale for clinical actionability of molecular targets (ESCAT) in advanced NSCLC. (24th November 2019) - Mezquita, L; Planchard, D; Suarez, M Dorta; Aldea, M; Naltet, C; Lamberts, V; Grecea, M; Martin-Romano, P; de Kievit, F; Jovelet, C; Lacroix, L; Masip, J Remon; et al.
Abstract: Background: The comprehensive genomic profile (CGP) by next generation sequencing (NGS) ctDNA can identify a wide spectrum of GA that range from drivers with approved targeted therapies for routine use to other GA with lack of evidence for actionability. We aimed to assess the clinical utility of NGS-ctDNA based on ESCAT in a large cohort of NSCLC patients. Methods: Advanced NSCLC patients were prospectively enrolled between 11.2015-05.2019 in the Liquid Biopsy Program in our institution. Plasma ctDNA was collected at diagnosis, under therapy or at progressive disease (PD) and analyzed by InVisionFirst TM Lung. We evaluated the detection of driver GA on ctDNA and the clinical utility for accessing targeted therapies approved for routine use (EGFR mutation (m), ALK rearrangement (r), BRAFV600Em, ROS1r), according to ESCAT tiers. Results: Preliminary results are available for 308 patients/547 samples (n = 117 untreated; 217 at PD). 58% were females, 42% nonsmokers, with median age of 61 (24-90) and 87% had adenocarcinoma. At diagnosis, ≥1 ctDNA GA was found in 79% (91/115; 2 failed analyses): 29% (26/91) were ESCAT tier I (16 EGFRm ex19/21, 1 ALKr, 1 ROS1r, 8 BRAFV600Em), 2% ESCAT tier II (2 METa ; 1 case co-driver with EGFRm) and 31% tier III (21 KRASm with 8 cases G12C; 5 HER2m, 2EGFRm ex20). ctDNA provided clinically informative results for 33% (38/115). At PD, ≥1 ctDNA GA was found in 75% (163/217); 2 failed analyses): 65% (106/163) in ESCAT tier I (66 EGFRm ex19/21, 7 ALKr, 32 BRAFV600Em, 1 ROS1r), <1% ESCAT tier II (1 METa) and 18% tier III (16 KRASm with 10 cases G12C; 10 HER2m, 3 EGFR others). ctDNA provided clinically informative results for 60% (130/217). We detected EGFR T790M in 49% (17/35) after 1st-2nd generation TKI, C797Sm in 75% (3/4) after Osimertinib and ALK mutations in 4/7 (57%) at TKI failure, with a total of 50% (21/42) cases where ctDNA provided clinical utility. Conclusions: ctDNA proved clinically informative results for 33% in untreated patients, most of them ESCAT tier I GA (22%) directing targeted therapies in routine. At time of TKI failure, ctDNA was clinically informative assessing resistance in 50% of EGFR/ALK patients. Legal entity responsible for the study: Gustave Roussy. Funding: Has not received any funding. Disclosure: L. Mezquita: Advisory / Consultancy: Roche Diagnostics; Honoraria (self): Bristol-Myers Squibb; Honoraria (self): Tecnofarma; Honoraria (self): Roche; Honoraria (self): AstraZeneca; Travel / Accommodation / Expenses: Chugai. D. Planchard: Advisory / Consultancy: Eli Lilly, Merck, Novartis, Pfizer, prIME Oncology, Peer CME, Roche; Honoraria (self): AstraZeneca, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Eli Lilly, Merck, Novartis, Pfizer, prIME Oncology, Peer CME, Roche; Research grant / Funding (institution): AstraZeneca, Bristol-Myers Squibb, Boehringer Ingelheim, Eli Lilly, Merck, Novartis, Pfizer, Roche, Medimmun, Sanofi-Aventis, Taiho Pharma, Novocure, Daiichi Sankyo; Travel / Accommodation / Expenses: AstraZeneca, Roche, Novartis, prIME Oncology, Pfizer; Advisory / Consultancy: AstraZeneca, Bristol-Myers Squibb, Boehringer Ingelheim, Celgene, Daiichi Sankyo, Eli Lilly, Merck, Novartis, Pfizer, prIME Oncology, Peer CME, Roche. F. de Kievit: Shareholder / Stockholder / Stock options: INIVATA Ltd. L. Lacroix: Advisory / Consultancy: Abbott, Astrazeneca, Boehringer Ingelheim, Bristol Myers Squibb, Ca Bayer Healthcarer, Illumina, Genomic Health, Myriad, Novartis, Pfizer, Roche, Siemens, Thermofisher, VelaDx. J. Remon Masip: Advisory / Consultancy: Pfizer, MSD, BMS, Astrazeneca, Boehringer Ingelheim; Travel / Accommodation / Expenses: OSE Immunotherapeutics, BMS, Astrazeneca, Roche; Honoraria (self): OSE Immunotherapeutics. P. Lavaud: Travel / Accommodation / Expenses: Astellas-Pharma, AstraZeneca, Ipsen, Janssen Oncology, Mundi Pharma. A. Gazzah: Travel / Accommodation / Expenses: Boehringer Ingelheim, Novartis, Pfizer, Roche; Advisory / Consultancy: Novartis; Research grant / Funding (institution), Clinical trials at Gustave Roussy: Aduro Biotech, Agios Pharmaceuticals, Amgen, Argen-X Bvba, Arno Therapeutics, Astex Pharmaceuticals, AstraZeneca, Aveo, Bayer Healthcare Ag, Bbb Technologies Bv, Beigene, Bioalliance Pharma, Biontech Ag, Blueprint Medicines, Boehringer Ingelheim, Bristol; Research grant / Funding (institution): AstraZeneca, BMS, Boehringer Ingelheim, Janssen Cilag, Merck, Novartis, Pfizer, Roche, Sanofi; Non-remunerated activity/ies, Drug supply: Astrazeneca, Bayer, BMS, Boringher Ingelheim, Johnson & Johnson, Lilly, Medimmune, Merck, NH TherAGuiX, Pfizer, Roche. C. Morris: Shareholder / Stockholder / Stock options: INIVATA Ltd. K. Howarth: Shareholder / Stockholder / Stock options: INIVATA Ltd. E. Green: Shareholder / Stockholder / Stock options: INIVATA Ltd. C. Massard: Advisory / Consultancy: Amgen, Astellas, AstraZeneca, Bayer, BeiGene, BMS, Celgene, Debiopharm, Genentech, Ipsen, Janssen, Lilly, MedImmune, MSD, Novartis, Pfizer, Roche, Sanofi, Orion; Research grant / Funding (institution), Clinical Trials at Gustave Roussy: AbbVie, Aduro, Agios, Amgen, Argen-x, Astex, AstraZeneca, Aveopharmaceuticals, Bayer, Beigene, Blueprint, BMS, Boehringer Ingelheim, Celgene, Chugai, Clovis, Daiichi Sankyo, Debiopharm, Eisai, Eos, Exelixis, Forma, Gamamabs, Genentech, Gortec, GSK, H3 biomed. B. Besse: Research grant / Funding (institution): AbbVie, Amgen, AstraZeneca, Biogen, Blueprint Medicines, BMS, Celgene, Eli Lilly, GSK, Ignyta, IPSEN, Merck KGaA, MSD, Nektar, Onxeo, Pfizer, Pharma Mar, Sanofi, Spectrum Pharmaceuticals, Takeda, Tiziana Pharma; Research grant / Funding (institution), Clinical Trials at Gustave Roussy: Nerviano, GSK, Pfizer, Roche-Genentech, Lilly, OSE Pharma, MSD, Celgene, Stemcentrx, Ignyta, AbbVie, Loxo Oncology, AstraZeneca, Blueprint Medicines. All other authors have declared no conflicts of interest.